Transient Political Infrastructures: Toward an Atlas of the Chilean Uprising. Issue 2 (3rd July 2022) - Jerrems, Ari; Landaeta, Patricio; Carmona Jiménez, Javiera
Abstract : The Chilean uprising has been defined by detractors and sympathizers as an " estallido social " or social explosion, alluding to its perceived transient character. Assumptions about spontaneity have similarly underpinned diagnoses of its political significance. It is either a problem to be pacified or limited for generating alternatives. This article problematizes this perceived transience, focusing instead on the event's rhythms, atmospheres and materialities. The article seeks to contribute to projects of collective knowledge production that underline the need to archive, map and theorise events as lived history. Studying the uprising as lived history does not elicit a particular response but rather initiates an investigation into what it makes possible. The figure of the atlas is developed for such an investigation. An atlas curates the emerging archive by composing images and text, not to close off meaning but rather allow for imagination to enter the realm of knowledge.